High-power, non-enzymatic glucose biofuel cell based on a nano/micro hybrid-structured Au anode - Chu, Tien-Fu; Rajendran, Raja; Kuznetsova, Iren; Wang, Gou-Jen (Journal of power sources, 2020)
In this study, a high-power, non-enzymatic glucose biofuel cell (GBFC) based on a nano/micro hybrid-structured Au anode is proposed. A uniformly distributed micro-hemispheric array of polycarbonate is fabricated for this novel electrode by hot embossing using a Ni mold. The nano/micro hybrid-structured Au anode is then fabricated by depositing an Au nanoparticle monolayer on the micro-hemispheric array using 1,6-hexanedithiol as a two-sided anchor. The cathode is composed of a graphene film-coated glassy carbon electrode. Nafion, a proton exchange membrane, is used to separate the anode and cathode and complete the battery assembly. Experimental results demonstrate that the proposed non-enzymatic GBFC has a high-power density of 10.7 mWcm−2, a high current density of 29.5 mAcm−2, an open-circuit voltage of 8.2 V, and a shorted-circuit current of 34 mA at room temperature. The energy conversion efficiency of the electrode is calculated to be 52.47%. In addition, the proposed GBFC possesses advantages such as ease of production on a large scale, low manufacturing cost, high repeatability, and long-term preservation. Therefore, it is highly feasible for commercialization and use in practical applications. •We develope a high-power non-enzymatic glucose biofuel cell.•The novel anode consists of a micro/nano hybrid structure of gold.•The monolayer of Au nanoparticles significantly enhances the glucose oxidation.•The current density of 29.5 mA/cm2 occurs at the power density of 10.7 mW/cm2.•The energy conversion efficiency was calculated to be 52.47%.